2013
DOI: 10.1332/174426413x671086
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge exchange between academia and the third sector

Abstract: This paper considers the different approaches to undertake knowledge exchange between academia and the third sector from three practitioner perspectives. London South Bank University (LSBU), as part of the Economic and Social Research Council (ESRC) and Third Sector Research Centre (TSRC) Social Enterprise Capacity Building Cluster (CBC), has been involved in a number of Knowledge Transfer Partnerships (KTP) and other capacity building projects. TSRC has developed an approach that offers a step change in the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 0 publications
0
16
0
1
Order By: Relevance
“…Using social media for information sharing reveals an interesting shift towards more informal means of knowledge exchange. Researchers in particular are said to benefit from this because social networking platforms allow for rapid and reactive knowledge exchange; and this can encourage engagement, discussion and feedback about a research topic (Murdock et al, 2013;Fahlberg, 2015).…”
Section: Using Twitter™ For Healthcare Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Using social media for information sharing reveals an interesting shift towards more informal means of knowledge exchange. Researchers in particular are said to benefit from this because social networking platforms allow for rapid and reactive knowledge exchange; and this can encourage engagement, discussion and feedback about a research topic (Murdock et al, 2013;Fahlberg, 2015).…”
Section: Using Twitter™ For Healthcare Researchmentioning
confidence: 99%
“…The Research Excellence Framework (REF) governs that researchers must consider how to engage with users, support pathways to impact and thus drive social and public benefit from M a n u s c r i p t 17 research. This is a crucial agenda for all universities (McKenna, 2015;Biswas and Kirchherr, 2015;Murdock, et al, 2013;McKenna, 2012).…”
Section: Can Twitter™ Help Researchers To Generate Impact?mentioning
confidence: 99%
“…Staff costs will constitute a significant portion of CAREN's funding footprint. There is a need for staff with different skills including a network manager for ongoing oversight and to maintain CAREN's sustainability, coherence, effectiveness and value for money (Murdock et al 2013). Other costs are likely to relate to bespoke IT software, rights clearances, broadband usage, supporting the consultation phase, fees for 'experts'…”
Section: The Challenges Of Realising Caren's Potentialmentioning
confidence: 99%
“…While effective knowledge transfer depends significantly on timing and context (Murdock et al 2013), certain practices have been shown to facilitate the research-to-policy process. For example, the involvement of research users from the beginning of a research project, along with the coproduction of knowledge during the project, increases research utilization (Murdock et al 2013;Patton and Blaine 2001). López Cerezo and González García (1996) argue that expert knowledge by itself is not sufficient for exerting policy influence because this knowledge is constrained by social, political and economic factors.…”
Section: Relationships Research Policymentioning
confidence: 99%